The Role Of Business Strategy As A Mediating Influence Of Entrepreneurial Orientation On UMKM Business Performance - Purnamasari, Pupung; Hariroh, Fiqih Maria Rabiatul; Putri, Fenina Berliana (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The purpose of this study is to examine the relationship between entrepreneurial orientation and business performance among Micro, Small, and Medium Enterprises (MSMEs), and to examine how business strategy mediates the relationship. The population in this study were business actors in Bekasi Regency in the Food & Bevarege sector. The sampling technique in this study was based on purposive sampling technique, namely regional sampling based on criteria. The criteria for selecting an area is to have a minimum of 100 business actors. The data collected is primary data through questionnaires and interviews. Data analysis was carried out using Smart PLS. The results of this study indicate that entrepreneurial orientation is positively related to MSME business performance, and that business strategy plays a mediating role in the relationship. The importance of developing entrepreneurial-compatible business strategies to improve MSME business performance is a significant implication of this finding